Analysis of Hypertension-Related Factors in Rural Areas, Banyumas Regency - Lu'lu Nafisah; Asti Nadia Anindita (Insights in Public Health Journal, 2023)
Background: Hypertension is a public health concern since it has the potential to cause consequences such as stroke, coronary heart disease, renal failure, and eventually become one of the leading causes of premature death worldwide. In many parts of Indonesia, notably rural regions, the prevalence of hypertension is relatively high. Information on hypertension risk factors in rural regions is required to develop effective interventions for the prevention and treatment of hypertension among rural communities. The purpose of this study is to investigate the risk factors associated with the prevalence of hypertension in rural areas. Methods: This research is a quantitative study using a case control approach with a total sample of 76 respondents. The comparison of the case and control groups in this study was 1:1.Questionnaires are used as instruments in data collection. The chi square test was used to assess the data. Results: Most of the respondents were in the late elderly age (35.5%), female (84.2%), had a family history of hypertension (40.8%), had normal BMI (30.3%), and obesity (28.9%). Most of the respondents did not smoke (93.4%), consumed less vegetables and fruit (78.9%), were not stressed (93.4%) and had sufficient levels of physical activity (82.9%).The findings revealed there was a relationship between age and hypertension (p value = 0.000). Gender (p = 0.753), family history of hypertension (p = 1,000), obesity (p = 0.502), smoking habit (p = 1,000), fruit and vegetable consumption (p = 0.778), level of stress (p = 1000), and physical activity (p = 0.542) were not linked with hypertension. Conclusions: Community health activities in rural regions must be strengthened in order to monitor public health status (including blood pressure monitoring) and approach the community to increase their involvement in these activities.